2014
DOI: 10.1002/hed.23592
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope‐assisted transoral approach to parapharyngeal space tumors

Abstract: This technique provided less operative trauma, a more comfortable postoperative period, and, most importantly, increased operative exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 15 publications
1
70
0
1
Order By: Relevance
“…Wang et al have reported that although PPS tumors may be completely removed by both external and transoral endoscopic approaches, the latter has the advantages of reduced blood loss and postoperative pain level and preservation of facial cosmetic. Similar results have been reported by Fan et al Endoscope‐assisted transoral resection provides a wider view, reducing the risks of neurovascular injury or capsule rupture and allowing resection of large tumors; those tumors surrounded major vascular structures or with large lateral extension are not suitable. Endoscopy may also be used to overcome some of the limitations of external conventional approaches .…”
Section: Surgerysupporting
confidence: 83%
See 2 more Smart Citations
“…Wang et al have reported that although PPS tumors may be completely removed by both external and transoral endoscopic approaches, the latter has the advantages of reduced blood loss and postoperative pain level and preservation of facial cosmetic. Similar results have been reported by Fan et al Endoscope‐assisted transoral resection provides a wider view, reducing the risks of neurovascular injury or capsule rupture and allowing resection of large tumors; those tumors surrounded major vascular structures or with large lateral extension are not suitable. Endoscopy may also be used to overcome some of the limitations of external conventional approaches .…”
Section: Surgerysupporting
confidence: 83%
“…Minimally invasive approaches have been advocated to minimize surgical morbidity while claiming complete PPS tumor resection. In general, the use of endoscopic approaches has not been standardized and should be used only in selected cases and performed by highly skilled surgeons . Wang et al have reported that although PPS tumors may be completely removed by both external and transoral endoscopic approaches, the latter has the advantages of reduced blood loss and postoperative pain level and preservation of facial cosmetic.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…CT can clearly depict the bone destruction and the relationship between the tumor and the pterygoid process. However, MRI is more sensitive and specific for differentiating benign and malignant diseases than CT, and provides more information . The coronal image demonstrates the position of PPS neoplasms and the relationship between PPS neoplasms and the hard palate clearly.…”
Section: Discussionmentioning
confidence: 99%
“…The purely transoral/transpharyngeal approaches are well known and widely used, especially in the treatment of benign deep lobe parotid tumors. Some reports have also focused on the possibility of improving visualization of the transoral surgical field with endoscopic assistance, thus enabling better identification of anatomic structures and improvements in tumor dissection with reduced risk of neurovascular injury or capsular rupture . When dealing with malignancies, however, the exclusive transoral approach should be limited to very selected lesions of the prestyloid compartment without superior extension toward the skull base or lateral extension beyond a virtual sagittal plane passing through the parapharyngeal tract of the ICA.…”
Section: Discussionmentioning
confidence: 99%